Improved lentiviral transduction of human mesenchymal stem cells for therapeutic intervention in pancreatic cancer - Kallifatidis, Georgios; Beckermann, Benjamin Michael; Groth, Ariane; Schubert, Mario; Apel, Anja; Khamidjanov, Akmal; Ryschich, Eduard; Wenger, Till; Wagner, Wolfgang; Diehlmann, Anke; Saffrich, Rainer; Krause, Ulf; et al. (Cancer gene therapy, 2008)
Genetic modification of human bone marrow mesenchymal stem cells (MSC) is highly valuable for their exploitation in basic science and therapeutic applications, for example in cancer. We present here a new, fast and easy-to-use method to enrich a functional population of lentiviral (LV)-transduced MSC expressing enhanced green fluorescent protein (eGFP). We replaced the eGFP gene by a fusion gene of puromycin acetyltransferase and eGFP. Upon LV gene transfer and puromycin selection, we quickly obtained a pure transduced MSC population, in which growth, differentiation capacity and migration preferences were not compromised. Furthermore, we are the first to report the migration velocity of MSC among which 30% were moving and velocity of about 15 μm h−1 was not altered by LV transduction. Manipulated MSC underwent senescence one passage earlier than non-transduced cells, suggesting the use for therapeutic intervention in early passage numbers. Upon tail vein application in nude mice, the majority of LV-transduced MSC could be detected in human orthotopic pancreatic tumor xenografts and to a minor extent in mouse liver, kidney and lung. Together, LV transduction of genes to MSC followed by puromycin selection is a powerful tool for basic research and improves the therapeutic prospects of MSC as vehicles in gene therapy.